Characterization and properties of binder and nano-filler in geopolymer paste with graphene oxide - A’lia Sofea Shamsol,; Nazirah Mohd Apandi,; Warid Wazien Ahmad Zailani,; Khairul Nazhan Khairul Izwan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Globally, current research has developed new cement-based materials to meet increased demands for performance, energy efficiency, and environmental protection. Geopolymer, cost-effective, and high-early strength concrete binder alternative, has grown in popularity. Geopolymer reduces emissions by 80% during production while maintaining strength levels comparable to Ordinary Portland Cement (OPC). In their natural state, geopolymer binders have a microstructure that is cross-linked and significantly more brittle than OPC. To improve the properties of geopolymer, several approaches were adopted. However, recent study suggests that incorporating nanomaterials such as graphene oxide (GO) to geopolymer has shown an improvement in physical and mechanical properties. Graphene oxide is an inorganic nanomaterial that improves the mechanical characteristics of various composite materials by showing substantial filling effects on composite materials that significantly improve composite material integrity. The investigation into the potential of GO to improve the efficacy of geopolymer composite materials in various engineering applications has garnered considerable attention in recent years. The simplified hummer’s method was employed to synthesise the GO. Various characterization techniques involving SEM, XRD, and FTIR were utilized to understand the crystalline structure and microstructure of GO nanoparticles. GO powder were used as 0.05%, 0.10%, 0.15%, 0.20%, and 0.25% by weight of binder that includes fly ash class F and steel slag with an optimum binder modification of 40% fly ash and 60% steel slag. The influence of GO on Bulk density, microstructure, and mechanical strength were determined. The compressive strength results indicated an improvement of compressive strength by 21.48% in geopolymer paste with 0.15% GO after 28 days of curing.